Miniaturized high-performance metallic 1T-Phase MoS2 micro-supercapacitors fabricated by temporally shaped femtosecond pulses. (January 2020) - Xu, Chenyang; Jiang, Lan; Li, Xin; Li, Chen; Shao, Changxiang; Zuo, Pei; Liang, Misheng; Qu, Liangti; Cui, Tianhong
Abstract: The recent development of wearable and portable microelectronic devices requires energy storage devices to be miniaturized; micro-supercapacitors (MSCs), as one of the most outstanding candidates, have great potential in future electronic devices. However, in the miniaturization of MSCs, the maintenance of electrochemical performance remains a key challenge. Herein, this study proposes a simple, one-step, mask-free and high-resolution fabrication method for high-performance 1T MoS2 MSCs in atmosphere. The method involves the direct writing of restacked 1T MoS2 films by a temporally shaped femtosecond laser. Specifically, femtosecond laser pulses are temporally shaped to control the transient electron temperature and material absorption for achieving high-resolution fabrication. Excellent electrode material properties and ultrashort ion transfer distance enable the MSCs to exhibit optimal performances with an ultrahigh power density (14 kW cm −3 ), ultrahigh energy density (15.6 mWh cm −3 ) and large areal capacitance (36 mF cm −2 ). Notably, such miniaturized MSCs in a 100 × 100 μm 2 area own superior frequency responses (1221 Hz) and time constant (0.82 ms), which are suitable for AC line filters and other high-power demanded electronic devices. This method successfully solves the problem of maintaining performance in the miniaturization of MSCs, allowing next-generation microelectronic devices to be developed. Graphical abstract: This study presents a simple, mask-free, and high-resolution approach to achieve miniaturized high-performance 1T MoS2 micro-supercapacitors through temporally shaped femtosecond laser direct writing. Non-thermal processing and phase transition control achieve ultrashort gap (833 nm) and abundant edges, miniaturizing energy storage devices while improving the electrochemical performance efficiently. Image 1 Highlights: A new method that uses temporally shaped femtosecond laser direct writing for fabrication of 1T MoS2 micro-supercapacitors. The MoS2 phase transition has been reduced effectively by non-thermal processing. The 1T MoS2 MSCs achieve the ~800 nm resolution and exhibit high electrochemistry performances. This method solves the key challenge of maintaining performance in the miniaturization of MSCs.